MATH ANXIETY: PROBLEMATICS AND CHALLENGES IN THE PROCESS OF TEACHING MATHEMATICS IN THE BASIC CYCLE - Silva Gusmão, Anderson; Cleyton Felipe Gaudêncio, Anderson; Bonifácio da Silva Júnior, João; Nestor Felipe Gaudêncio, Robson (Journal of Interdisciplinary Debates, 2024)
Mathematics anxiety has been the subject of growing academic interest, as it can significantly impact academic performance and individuals’ relationship with mathematical content throughout their lives. This narrative review aims to understand the conceptual evolution, causes and possible interventions associated with mathematics anxiety. Using a bibliographic methodology, articles, books and reports published in renowned academic databases were analyzed. As the main theoretical framework, the cognitive-behavioral perspective was adopted, which understands mathematical anxiety as a result of interactions between cognitive, behavioral and environmental processes. The results point to a multifaceted understanding of the phenomenon, highlighting not only individual factors, such as self-efficacy and past experiences, but also external factors, such as teaching methods and teachers’ attitudes. Interventions aimed at reducing mathematics anxiety have focused on both pedagogical strategies and psychotherapeutic approaches, demonstrating the need for an interdisciplinary approach to tackle the problem. This work contributes to the literature by consolidating dispersed knowledge and indicating future paths for educational research and practice.